Environmentalism and cultural theory exploring the role of anthropology in environmental discourse - Milton, Kay 1951- (London Routledge, 1996)
The last decade has seen a dramatic increase in the attention paid by social scientists to environmental issues, and a gradual acknowledgement in the wider community, of the role of social science in the public debate on sustainability. At the same time, the concept of "culture", once the property of anthropologists, has gained wide currency among social scientists. The book shows how an understanding of culture can throw light on the way environmental issues are perceived and interpreted, both by local communities and within the contemporary global arena. Taking an anthropological approach, the book examines the relationship between human culture and human ecology, and considers how a cultural approach to the study of environmental issues differs from other established approaches in social science. This book adds significantly to our understanding of environmentalism as a contemporary phenomenon, by demonstrating the distinctive contribution of social and cultural anthropology to the environmental debate.
Introduction: Social science and environmental discourse -- Anthropology, culture and environmentalism -- Culture and ecology -- Environmentalism in social science -- Environmentalism and cultural diversity -- Globalization, culture and discourse -- The culture of global environmentalist discourse -- Anthropology, social science and environmentalism.
Includes bibliographical references (pages 236-256) and index.
Keywords: Environmentalism -- Social aspects; Culture; Ethnology